MAULID NABI CELEBRATION ARENA IN THE CONTEXT OF SOCIAL SCIENCE (International Conference on Social and Islamic Studies, 2021)
The celebration to commemorate Prophet Muhammad’s Birthday knows as Maulid Nabi, which held at Bangkalan, Madura, exhibit a capital clash within Madurese’s societal culture. Maulid Nabi celebration or in local language called Muludhen, demonstrate four capitals explained by Bourdieu which possessed by Madurese peoples. This study employed descriptive qualitative method, with every person from each social class as a key informant. Muludhen celebration displayed a rare spectacle of Madurese’s genuine cultural identity, which are eroded by bourgeoism and in local language “tertekan dhibik”. The festivities of the Muludhen celebration, goes hand in hand with the economical level in the Madurese Society. The contention of the Bourdieu’s four capitals, held to exhibit their societal status within the Madurese Society. Nevertheless, Muludhen which are held at the Mosque or at the private property like local people’s house, held one major intention; to preserve harmony and fraternity within Madurese Society.